Innovation in Isolation? COVID-19 Lockdown Stringency and Culture-Innovation Relationships - Kapoor, Hansika; Ticku, Arunima; Tagat, Anirudh; Karandikar, Sampada (Frontiers in Psychology, 2021)
In a bid to curb the spread of COVID-19 in 2020, several countries implemented lockdown procedures to varying degrees. This paper sought to examine the extent to which country-level strictness, as measured by the Government Response Stringency Index (2020), moderated the relationship between certain cultural dimensions and estimates of national innovation. Data on 84 countries were collated for Hofstede’s cultural dimensions (2015), and from the Global Innovation Index (2020). Owing to the robust relationships between innovation and the dimensions of uncertainty avoidance, power distance, and individualism, these were used in moderation analyses. In general, power distance was inversely related to innovation, whereas individualism was directly related to it. Results indicated that collectivist and high power distance countries showed lower innovation, irrespective of levels of government stringency as a response to COVID-19. On the other hand, among individualistic and low power distance countries, lower innovation was associated with increased stringency (e.g., blanket restrictions on movement). Higher innovation was observed when such countries had a less severe government response. The dimension of uncertainty avoidance was not significantly associated with innovation at the country level. The implications of lockdowns on general innovation, its inputs, and outputs are discussed in the context of cultural dimensions and country-level policies.